Analysis of Millennial Generation Behavior in Consuming Halal Products: Structural Equation Model-Partial Least Square (SEM-PLS) Method - Arifin, Ahmad Zaenal; Salam, Annisa Nur (Ekonomi Syariah IAIN Kudus, 2019)
The elevated demand of Muslim consumers for halal products is a business opportunity for producers or companies. So that attention to consumer behavior of halal products is part of market valuation that is important for achieving success in the halal industry. Meanwhile, the millennial generation will have an influence in determining the trend of product use especially since entering the digital era. So it is important to conduct further studies on the behavior of the millennial generation in consuming halal products. This research was conducted by collecting data through distributing questionnaires to 100 respondents classified as millennial generation. Then the data collected is processed with Structural Equation Modeling-Partial Least Square (SEM-PLS) and gives conclusion that the interest of millennial generation in buying halal products is influenced by Islamic branding and individual religiosity factors. While the satisfaction of the millennial generation in consuming halal products is influenced by the price factor of these products, Islamic branding and religiosity factors. Furthermore, Islamic branding indirectly influences the buying interest and satisfaction of the millennial generation in consuming halal products through a variable mediating religiosity. Therefore, Islamic branding is an urgent matter that must be fulfilled for companies that have a focus on the development of halal industrial.